Prenatal Yoga untuk Mengatasi Ketidaknyamanan Ibu Hamil - Tasuib, Maria Jessyca; Ulfi Amalia; Hapsari Windayanti; Widayati (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
Prenatal yoga is a skill to process the mind, in the form of a comprehensive personality development technique and the readiness of pregnant women both physically, psychologically and spiritually. Pregnant women are said to be physically ready if they are not easily tired, weak, flexibility and endurance increase and decrease back pain. Yoga counseling for pregnant women as an effort to reduce back pain in Medayu Village, Suruh District, Semarang Regency which was attended by 10 pregnant women. The implementation of Community Service was carried out on Monday, June 10, 2024 offline, with a method with an introduction first, then filling out the pre test, then presenting the material and continuing with a yoga demonstration, then a question and answer process, then filling out the post test, and finally closing. Counseling participants understand and understand how to do pregnancy yoga to reduce back pain in pregnant women and can establish communication between the proposing team and the mothers who carry out counseling. There is an increase in the knowledge and skills of mothers, as seen from the data of the percentage of good 100%(post test). It is hoped that mothers can practice yoga for pregnant women at home independently to overcome back pain and participants will feel enthusiastic about their presence, responsibility and practicing yoga for pregnant women.   Abstrak Prenatal yoga merupakan keterampilan mengolah pikiran, berupa teknik pengembangan kepribadian secara menyeluruh dan kesiapan ibu hamil baik fisik, psikologis dan spiritual. Ibu hamil dikatakan siap secara fisikapabila tidak mudah lelah, lemas, fleksibilitas dan daya tahan tubuh meningkat dan penurunan nyeri punggung. Penyuluhan yoga ibu hamil sebagai upaya untuk mengurangi nyeri punggung di Desa Medayu, Kecamatan Suruh, Kabupaten Semarang yang di ikuti 10 ibu hamil. Pelaksanaan Pengabdian Masyarakat dilakukan Hari Senin, 10 Juni 2024 secara luring (offline), dengan metode dengan perkenalan terlebih dahulu selanjutnya pengisian pre test, kemudian pemaparan materi dan dilanjutkan demonstrasi yoga, berikutnya proses tanya jawab kemudian pengisian post test dan terakhir penutup. Peserta penyuluhan mengerti dan memahami cara melakukan Yoga hamil Untuk mengurangi nyeri punggung pada ibu hamil dan bisa terjalin komunikasi baik tim pengusul dan para ibu yang melakukan penyuluhan. Terdapat peningkatan pengetahuan dan keterampilan ibu-ibu, yang dilihat dari data presentase baik 100%(post test). Diharapkan ibu-ibu dapat mempraktikkan yoga ibu hamil dirumah secara mandiri dalam mengatasi nyeri punggung serta peserta merasa antusias dalam kehadiran, bertanggungjawab dan mempraktikkan yoga ibu hamil.